Everyday life as an object of scientific research - Aimahov, E.N. (Ye.A.Buketov Karaganda State University Publ., 2014)
Essentially the history of society is a person's everyday life in its historical dimension, which is reflecting certain immutable properties and quality in accordance with the fixation of new forms of housing, food, travel, work and leisure. The clue lies exactly in the analysis of everyday life; it gives answers to the question arisen often when we meet with specific fates: how people could survive and preserve human dignity in the extreme conditions of revolutions, wars, terror, hunger and devastation? How people adapted to some life circumstances? Everyday life is an object of scientific research for a range of humanities disciplines, among which there is no consensus even in the definition of the concept of «everyday life». The article analyzes some problems of the history of everyday life. It generalizes and systematizes the scientists’ opinions on the content and structure of concept «social everyday life». The author determines questions of social everyday life which are relatively good investigated. These are the questions of household, free time and lifestyle of people.
Күнделікті өмір тарихы ғылыми зерттеу объектісі ретінде
Повседневность как объект научного исследования
Keywords: everyday life; the history of everyday life; sociology; the sociology of everyday life; the world of everyday life; daily interaction; historical anthropology; micro-history; the sphere of routine